Nocturnal stray dogs that pass through the streets of the Historic Center of Lima - Peru - Leyva Ayón, Kaori (2022)
The objective of the study was to estimate the population and describe the demographic characteristics and welfare status of the dogs that move freely through the streets of the Historic Center of Lima at night. For this, an observational, cross-sectional and descriptive study was carried out. For this, the Plan of the Municipality of Cercado de Lima was taken into consideration, which was divided into six blocks using the following limits: in a transverse line Av. Tacna, Jr. De la Unión and Av. Abancay; and transversally the blocks with Jr. Moquegua and Jr. Huallaga will be limited. Each of the blocks was evaluated on a specific day. Three measurements were made for each sector on 3 consecutive days from 10:00 p.m. to 12:00 a.m. Information on number, size (small, medium, and large), sex (female, male, and undetermined), body condition (acceptable, skinny, or obese), lameness (yes, no), and skin condition (with or without visible lesions). The information obtained from the study was summarized using descriptive statistics. The study found a total average of 38 stray dogs and an estimated mean of 3.7 stray dogs per Km2 and 26 stray dogs per 100,000 inhabitants. The predominant characteristics of the stray dogs were male, large size and fair condition. The presence of skin lesions and signs of lameness was minimal. Based on the results, actions can be taken to comply with Law 27596, Law that Regulates the Legal Regime of Dogs in order to reduce the presence of stray dogs in the Historic Center of Lima.